The Effect of Laparoscopic Sleeve Gastrectomy on Serum Iron Level - Masood Amini; Afshin Zare; Zahra Sobhani; Seyedeh Sara Hashemi; Leila Vafa (International Journal of Nutrition Sciences, 2018)
Background: Sleeve gastrectomy surgery is effective in limiting food intake and sometimes unknown and hormonal causes in weight loss. After the bariatric surgery, patients may be exposed to nutritional deficiencies, especially iron deficiency. Regarding the importance of iron in body metabolism, this study aimed to investigate the effect of Sleeve Gastrectomy surgery on the level of serum iron deficiency anemia. Methods: This cross-sectional study of 218 patients who underwent sleeve gastrectomy surgery for obesity from April 2017 to July 2018 in Shiraz Ghadir Mother & Child Hospital, which were studied in a quarterly period. The indications of the surgery were having BMI> 40 or between 35 and 39.9, which were associated with an co morbid disease. Serum levels of hemoglobin, iron, and ferritin before and three months after the surgery were evaluated. Results: The mean±SD of serum iron level in women ranged from 68.8±1.91 to 65.9±2.7 and in mean±SD from 74.6±5.32 to 71.7±2.8, and the mean serum ferritin level in women was from 56.1±5.5 to 43.2±6.1, and in males, from 61.9±9.7 to 47.3±8.2, and the mean±SD of serum hemoglobin level in both women and men was from 11.8±0.13 to 12.7±0.09 to 10.7±0.12 to 11.7±0.08 and from 12.7±0.09 to 11.8±0.13 to 11.7±0.08 to 10.7±0.12, respectively. Conclusion: The results of this study indicate that due to the reduction of the level of iron, after the sleeve gastrectomy surgery, the iron level of the patients should be regularly checked in order to be able to administer adequate supplements and to adjust the diet which is rich in iron to prevent anemia and its effects.